2020
DOI: 10.1111/bjd.18794
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting pachyonychia congenita: a case‐cohort study of 815 patients

Abstract: Summary Background Pachyonychia congenita (PC) is a group of autosomal dominant disorders caused by mutations in one of five keratin genes (KRT6A, KRT6B, KRT6C, KRT16, KRT17). The establishment of an international registry containing clinical and molecular data led to the development of a disease classification based on the mutant gene and associated features. Objectives To harness the same resource to clarify the prevalence of PC‐associated clinical features, delineate phenotype–genotype correlations and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 37 publications
5
39
1
6
Order By: Relevance
“…18 By contrast, nail dystrophy was evident in only 81% of our patients compared with 96% of patients reported in the IPCRR. 18 Pilosebaceous cysts were found in 29% of our patients, a similar rate to IPCRR, 18 whereas oral leucokeratosis was observed in only 31% of cases, compared with the rate of 54% reported in the IPCRR. The prevalence of prenatal/natal teeth in our cohort was similar to that in the IPCRR (13% and 14%, respectively) (Table 3).…”
Section: Clinical Manifestations Of the Israeli Pachyonychia Congenita Cohortcontrasting
confidence: 67%
“…18 By contrast, nail dystrophy was evident in only 81% of our patients compared with 96% of patients reported in the IPCRR. 18 Pilosebaceous cysts were found in 29% of our patients, a similar rate to IPCRR, 18 whereas oral leucokeratosis was observed in only 31% of cases, compared with the rate of 54% reported in the IPCRR. The prevalence of prenatal/natal teeth in our cohort was similar to that in the IPCRR (13% and 14%, respectively) (Table 3).…”
Section: Clinical Manifestations Of the Israeli Pachyonychia Congenita Cohortcontrasting
confidence: 67%
“…Abnormal expression of KRT17 has been found in various dermatoses, including psoriasis, alopecia, and pachyonychia congenita (PC) ( 38 ). The genetic mutation in KRT17 is related to PC, which mainly manifests itself as hyperkeratosis of the nails, palm, and pelma ( 39 ). Meanwhile, microarray analysis of non-healing chronic ulcers identified that the KRT17 gene was significantly downregulated relative to expression levels in healing chronic ulcers ( 40 ), suggesting that dysregulation of KRT17 is involved in defective healing.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PC present with nail thickening and painful plantar keratoderma. Additional features include hyperhidrosis, oral leukokeratosis, follicular keratosis, palmar keratoderma, cutaneous cysts, hoarseness or laryngeal involvement, coarse or twisted hair and abnormalities of the teeth 1 . Current treatment focuses on symptom relief 2 .…”
Section: Figurementioning
confidence: 99%
“…Pachyonychia congenita is a keratinopathy caused by pathogenic variants in one of four genes, namely KRT6A, KRT6B, KRT16 or KRT17 1,6 . The dominant negative effect of amino acid substitutions leads to aggregation of keratin intermediate filaments and to mechanical fragility of keratinocytes.…”
Section: Figurementioning
confidence: 99%